Dating Quaternary Deposits by Luminescence - Recent Advances - Berger, G. (Geoscience Canada, 1986)
Summary The use of thermoluminescence (TL) for dating Quaternary sediments (both heated and unheated) is expanding rapidly, and is poised to become routine for deposits previously considered barren of datable material or that are inaccessible to other absolute chrono-metric methods (e.g. "C, K-Ar, fission-track dating). Especially significant advances in procedures, applications, understanding and technology have been made within the pastf ew years. It is now possible to date the cooling of airfall glass in tephra, and the last exposure to light of feldspars within loess, buried soils and in some waterlaid silts. Sand-sized quartz from beach and dune deposits, and silt-sized feldspar from peats, offer potential. Perhaps outshining this substantial progress in application of TL methods to un-healed sediments is a potentially revolutionary technique, demonstrated at Simon Fraser University, that uses laser light rather than heat to stimulate the luminescent signal inminerals. This new technique is expected to be sensitive, simple and speedy. Furthermore, it has the potential to date unheated sediments that have received very brief (e.g.minutes) exposure to sunlight at deposition time.